In Vitro Effect of 9,9′-Norharmane Dimer against Herpes Simplex Viruses - Gonzalez, Maria Micaela (2024)
Herpes simplex virus (HSV) infections are highly widespread among humans, producingsymptoms ranging from ulcerative lesions to severe diseases such as blindness and life-threateningencephalitis. At present, there are no vaccines available, and some existing antiviral treatments canbe ineffective or lead to adverse effects. As a result, there is a need for new anti-HSV drugs. In thisreport, the in vitro anti-HSV effect of 9,9′-norharmane dimer (nHo-dimer), which belongs to the β-carboline (βC) alkaloid family, was evaluated. The dimer exhibited no virucidal properties and didnot impede either the aachment or penetration steps of viral particles. The antiviral effect was onlyexerted under the constant presence of the dimer in the incubation media, and the mechanism ofaction was found to involve later events of virus infection. Analysis of fluorescence lifetime imagingdata showed that the nHo-dimer internalized well into the cells when present in the extracellularincubation medium, with a preferential accumulation into perinuclear organelles including mitochondria.After washing the host cells with fresh medium free of nHo-dimer, the signal decreased,suggesting the partial release of the compound from the cells. This agrees with the observation thatthe antiviral effect is solely manifested when the alkaloid is consistently present in the incubationmedia.